Tracking tourist movement and migration - Hardy, Anne (Oxford Goodfellow Publishers Limited, 2020)
The first text to address tourist movement in from a methodological angle in the post-digital era. It assesses how movement and migration has been recorded in the past, how it may be recorded and assessed now and the possibilities for exploring movement in the future.
Includes bibliographical references and index.
Keywords: Tourism -- Technological innovations; Culture and tourism